How to interpret an unenhanced CT Brain scan. Part 2: Clinical cases - Thomas Osborne; Christine Tang; Kivraj Sabarwal; Vineet Prakash (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2016)
The aim of this article is to illustrate common pathological findings involving the brain encountered in every day practice. This builds upon our first article titled "How to interpret an unenhanced CT Brain scan. Part 1: Basic principles of Computed Tomography and relevant neuroanatomy"